2015
DOI: 10.1111/cobi.12556
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating climate‐change‐induced range shifts across continental land‐use barriers

Abstract: Climate changes impose requirements for many species to shift their ranges to remain within environmentally tolerable areas, but near-continuous regions of intense human land use stretching across continental extents diminish dispersal prospects for many species. We reviewed the impact of habitat loss and fragmentation on species' abilities to track changing climates and existing plans to facilitate species dispersal in response to climate change through regions of intensive land uses, drawing on examples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 95 publications
(185 reference statements)
1
72
0
1
Order By: Relevance
“…The fourth principle, connectivity, promotes natural movements for wide-ranging species (see Di Minin et al 2016), prevents breeding populations from becoming isolated (Haddad et al 2015;Belote et al 2016), and facilitates south-to-north and elevational movement of individuals that are shifting geographically in response to changing climates Robillard et al 2015). Long-term experiments have shown that fragmentation of landscapes reduces biodiversity by 13%-75%, lowering species' abundance and persistence times (Haddad et al 2015, Coristine et al…”
Section: Principle 4: Ensure Connectivity and Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…The fourth principle, connectivity, promotes natural movements for wide-ranging species (see Di Minin et al 2016), prevents breeding populations from becoming isolated (Haddad et al 2015;Belote et al 2016), and facilitates south-to-north and elevational movement of individuals that are shifting geographically in response to changing climates Robillard et al 2015). Long-term experiments have shown that fragmentation of landscapes reduces biodiversity by 13%-75%, lowering species' abundance and persistence times (Haddad et al 2015, Coristine et al…”
Section: Principle 4: Ensure Connectivity and Resiliencementioning
confidence: 99%
“…Climatically stable areas ("climate refugia") foster the persistence of biological communities (Iwamura et al 2010) and facilitate population movement from current to future suitable habitat (Robillard et al 2015;Coristine et al 2016;McGuire et al 2016). …”
Section: Principle 5: Preserve Climate Refugiamentioning
confidence: 99%
See 1 more Smart Citation
“…For eButterfly, project design is based on the formation of scientific questions, followed by the recruitment of participants to collect the data necessary to answer those questions. eButterfly focuses on scientific inquiry in changes in biodiversity, effects of climate change, and butterfly conservation from regional to continental scales [14,28,29]. Specifically, we are interested in how climate and land use change alters butterfly distributions, abundances, phenologies, and community structure in space and time.…”
Section: Data Quality and Quantity Can Be Improved And Managed In mentioning
confidence: 99%
“…In this context, and according to the island biogeography theory (MacArthur and Wilson 1967), we can consider microrefugia (or perfugia) as patches of suitable habitats which may or may not be inhabited by relict populations at a certain period. The occupation of suitable sites which can play a role in species range shift depends in a meaningful way on the dispersal effectiveness (Robillard et al 2015); hence, some sets of suitable sites can only play a potential role. As mentioned above, in regions where general conditions are projected to became unsuitable for the analyzed taxa, it is only possible to model potential, locallysuitable sites (e.g.…”
Section: The Road To Microrefugia: Linking Ecology and Evolutionmentioning
confidence: 99%